2018
DOI: 10.1016/j.jgeb.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Inter and intraspecific genetic diversity (RAPD) among three most frequent species of macrofungi ( Ganoderma lucidum , Leucoagricus sp. and Lentinus sp.) of Tropical forest of Central India

Abstract: In present study seven RAPD primers were used to access the diversity within and among twelve populations of three mushroom species Ganoderma lucidum, leucoagaricus sp. and Lentinus sp. Total of 111 bands were scored by 7 RAPD primers in 30 accessions of three mushroom species collected from different sampling sites of central India. Total 111 bands were generated using seven primers which were F-1, OPG-06, OPC-07, OPD-08, OPA-02, OPD-02, OPB-10. All 111 bands were polymorphic in nature (100%). Therefore, it r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Figure 4 showed that RAPD markers can show genetic variation in nine Rhizopus. Previously it has been reported that RAPD marker can be used as an important technique to investigate for the genetic variations of fungal (Dwivedi et al 2018). These reported are in line with our result, where RAPD marker can also distinguish the genetic variations of nine R. microsporus and two R. delemar well.…”
Section: Discussionsupporting
confidence: 92%
“…Figure 4 showed that RAPD markers can show genetic variation in nine Rhizopus. Previously it has been reported that RAPD marker can be used as an important technique to investigate for the genetic variations of fungal (Dwivedi et al 2018). These reported are in line with our result, where RAPD marker can also distinguish the genetic variations of nine R. microsporus and two R. delemar well.…”
Section: Discussionsupporting
confidence: 92%
“…The RAPD assay is a common and useful method for the identification of fungal strains and for the identification of Ganoderma lucidum strains [ 45 , 46 ]. It is often used in mutagenesis identification as well [ 34 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Though RAPD markers have the problem of reproducibility, until recently and till to date these are the proven markers in terms of cost effectiveness that were extensively used to study genetic diversity among the species of bacteria, fungi, insects, plants and animals. Genetic diversity of twelve populations of three mushroom species were evaluated using seven RAPD markers that were able to differentiate the percent variability within and among different populations of these mushroom species (Dwivedi et al, 2018). Sugarcane when genetic diversity was estimated contain similarity coefficient which ranged from 0.43 to 0.91 using thirty five RAPD markers while the ISSR primers could explain the similarity coefficient from 0.73 to 0.93 which is less compared to RAPD markers (Patel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%